Simulation and thermodynamic analysis of extended expansion on a concept rotary engine including its effects on fuel efficiency. Issue 1 (1st January 2017) - Andre, Denis Allemant; Jensen, Matthew James; Micklow, Gerald; Brenner, James; Helldorff, Helgevon
Abstract: This paper describes a novel method for extended expansion in a rotary combustion engine running ordinary gasoline. The engine consists of a toroidal-shaped piston that rotates around a drum to expand and evacuate the hot gas. There are several problems with today's internal combustion (IC) engines. Current IC engines do not always have the necessary internal volume to extract the maximum work possible, and since the whole process of compression, combustion, and expansion happen within the same space, excess heat builds up and increases emissions of nitric oxides and nitrogen dioxide. The proposed solution is to redesign the IC engine in order to supply greater expansion ratio by separating the compression and expansion processes. With the concept rotary engine, extending the expansion process showed improvements in the thermal and fuel efficiencies. Using a stroke length between 20 and 25 cm with a compression ratio of 10:1 produced the most efficient results with an efficiency range between 32 and 35%.